VALIDITY AND EFFECTIVENESS OF DEVELOPING PROCEDURE TEXT ITEMS USING WORDWALL LEARNING MEDIA FOR GRADE VII STUDENTS OF 12TH STATE JUNIOR HIGH SCHOOL IN MAKASSAR - Nur Hidayah Rusli; Munirah Munirah; Muhammad Agus (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
The validity and effectiveness of the development of procedural text questions using Wordwall learning media in grade VII students at SMP Negeri 12 Makassar is a research aimed at determining the validity and effectiveness of the use of Wordwall media as an evaluation media in the form of questions in procedural text learning for grade VII students of SMP Negeri 12 Makassar, specifically referring to the independent curriculum. The research is a research and development (R&D) using quantitative descriptive analysis method. The 4D model is used, which includes the stages of define, design, development, and disseminate. The subjects of the study are Indonesian language material experts, media experts, students, and educators using questionnaires and evaluation sheets. The data collection techniques used in this study are observation, interviews, and questionnaires. The sample determination in this study uses the Slovin model. The results of this study indicate that the implementation of procedural text questions on Wordwall learning media is considered valid by validators selected by the researcher and has met the qualifications to assess learning media, stating that 96% of the questions in this media are very feasible, while the media assessment is also very feasible with a percentage of 100%, so it is recommended to be used in the evaluation process of Indonesian language learning, especially in the procedural text sub-material for grade VII students of SMP Negeri 12 Makassar from various aspects. The effectiveness of the media is assessed based on the scores obtained by students on the questions provided in Wordwall media, which can be answered with an average score of 17 out of 19 questions or 89% of students get a satisfactory score, so it is considered very effective. In addition, the Worwall learning media is considered very interesting with a percentage of 92.7% so it can be used as an alternative learning media. The 4D model used has been carried out and fulfilled as a whole